Faster than Fourier ultra-efficient time-to-frequency-domain conversions for FDTD simulations. - Furse, Cynthia M. (IEEE Antennas & propagation magazine.)
This tutorial compares several methods of converting from the time to the frequency domain for FDTD simulations. Applications include calculations of field or power distributions, antenna impedance, and radiation patterns. The traditional Fourier-transform methods are compared to two methods based on the solution of linear equations. This tutorial describes how to program and use these techniques, and evaluates their effectiveness for several applications, including analysis of a millimeter-resolution human model underneath a 60-Hz power line, antenna-radiation pattern and impedance calculations, the calculation of the coupling of a cellular telephone to the human head, and geophysical-prospecting simulations.